(untitled) (Journal of Chitwan Medical College, 2026)
Introduction: Postoperative ileus (POI) is a common complication following abdominal surgery, contributing to prolonged hospitalization and increased morbidity. Chewing gum may enhance postoperative gastrointestinal recovery through cephalic-vagal stimulation. This study aimed to evaluate the effectiveness of gum-chewing in reducing the duration of POI after abdominal surgery. Method: A quasi-experimental study was conducted from 1 Apr 2019 to 30 Mar 2020 at BPKIHS, Dharan, Nepal. Patients undergoing abdominal surgery were allocated to experimental (n=20) or control (n=20) groups by lottery. The experimental group chewed sugarless gum for 30 minutes every 8 hours postoperatively until first flatus, in addition to standard care. The control group received standard care only. Primary outcomes were time to first bowel sound, flatus, and defecation. Data were analysed using SPSS 11.5 with descriptive and inferential statistics (Mann-Whitney U test, Chi-square, Spearman’s correlation). A p≤0.05 was considered significant. Result: Among 40 patients, median time to first bowel sound was 36 h (IQR 24-52.5) in the gum-chewing group versus 51 h (IQR 36-75) in controls (p=0.05). Time to first flatus was 40.75 h (IQR 24-61.75) versus 56.75 h (IQR 46.63-83.5) (p=0.02). Time to first defecation was 60.5 h (IQR 44.25-79) versus 73.5 h (IQR 62.75-102) (p=0.04). No significant difference was found in hospital stay or socio-demographic associations (p>0.05). Conclusion: Gum-chewing significantly accelerates the return of bowel function after abdominal surgery and is an effective adjunct to postoperative care.